Neoadjuvant treatment for stage III and IV cutaneous melanoma - Mc Cullagh, Laura; Coyne, Imelda (My University, 2023)
Background: Cutaneous melanoma is amongst the most aggressive of all skin cancers. Neoadjuvant treatment is a form of induction therapy, given to shrink a cancerous tumour prior to the main treatment (usually surgery). The purpose is to improve survival and surgical outcomes. This review systematically appraises the literature investigating the use of neoadjuvant treatment for stage III and IV cutaneous melanoma. Objectives: To assess the effects of neoadjuvant treatment in adults with stage III or stage IV melanoma according to the seventh edition American Joint Committee on Cancer (AJCC) staging system. Search methods: We searched the following databases up to 10 August 2021 inclusive: Cochrane Skin Specialised Register, CENTRAL, MEDLINE, Embase, LILACS and four trials registers, together with reference checking and contact with study authors to identify additional studies. We also handsearched proceedings from specific conferences from 2016 to 2020 inclusive. Selection criteria: Randomised controlled trials (RCTs) of people with stage III and IV melanoma, comparing neoadjuvant treatment strategies (using targeted treatments, immunotherapies, radiotherapy, topical treatments or chemotherapy) with any of these agents or current standard of care (SOC), were eligible for inclusion. Data collection and analysis: We used standard Cochrane methods. Primary outcomes were overall survival (OS) and adverse effects (AEs). Secondary outcomes included time to recurrence (TTR), quality of life (QOL), and overall response rate (ORR). We used GRADE to evaluate the certainty of the evidence. Main results: We included eight RCTs involving 402 participants. Studies enrolled adults, mostly with stage III melanoma, investigated immunotherapies, chemotherapy, or targeted treatments, and compared these with surgical excision with or without adjuvant treatment. Duration of follow-up and therapeutic regimens varied, which, combined with heterogeneity in the population and definitions of the endpoints, precluded meta-analysis of all identified studies. We performed a meta-analysis including three studies. We are very uncertain if neoadjuvant treatment increases OS when compared to no neoadjuvant treatment (hazard ratio (HR) 0.43, 95% confidence interval (CI) 0.15 to 1.21; 2 studies, 171 participants; very low-certainty evidence). Neoadjuvant treatment may increase the rate of AEs, but the evidence is very uncertain (26% versus 16%, risk ratio (RR) 1.58, 95% CI 0.97 to 2.55; 2 studies, 162 participants; very low-certainty evidence). We are very uncertain if neoadjuvant treatment increases TTR (HR 0.51, 95% CI 0.22 to 1.17; 2 studies, 171 participants; very low-certainty evidence). Studies did not report ORR as a comparative outcome or measure QOL data. We are very uncertain whether neoadjuvant targeted treatment with dabrafenib and trametinib increases OS (HR 0.28, 95% CI 0.03 to 2.25; 1 study, 21 participants; very low-certainty evidence) or TTR (HR 0.02, 95% CI 0.00 to 0.22; 1 study, 21 participants; very low-certainty evidence) when compared to surgery. The study did not report comparative rates of AEs and overall response, and did not measure QOL. We are very uncertain if neoadjuvant immunotherapy with talimogene laherparepvec increases OS when compared to no neoadjuvant treatment (HR 0.49, 95% CI 0.15 to 1.64; 1 study, 150 participants, very low-certainty evidence). It may have a higher rate of AEs, but the evidence is very uncertain (16.5% versus 5.8%, RR 2.84, 95% CI 0.96 to 8.37; 1 study, 142 participants; very low-certainty evidence). We are very uncertain if it increases TTR (HR 0.75, 95% CI 0.31 to 1.79; 1 study, 150 participants; very low-certainty evidence). The study did not report comparative ORRs or measure QOL. OS was not reported for neoadjuvant immunotherapy (combined ipilimumab and nivolumab) when compared to the combination of ipilimumab and nivolumab as adjuvant treatment. There may be little or no difference in the rate of AEs between these treatments (9%, RR 1.0, 95% CI 0.75 to 1.34; 1 study, 20 participants; low-certainty evidence). The study did not report comparative ORRs or measure TTR and QOL. Neoadjuvant immunotherapy (combined ipilimumab and nivolumab) likely results in little to no difference in OS when compared to neoadjuvant nivolumab monotherapy (P = 0.18; 1 study, 23 participants; moderate-certainty evidence). It may increase the rate of AEs, but the certainty of this evidence is very low (72.8% versus 8.3%, RR 8.73, 95% CI 1.29 to 59; 1 study, 23 participants); this trial was halted early due to observation of disease progression preventing surgical resection in the monotherapy arm and the high rate of treatment-related AEs in the combination arm. Neoadjuvant combination treatment may lead to higher ORR, but the evidence is very uncertain (72.8% versus 25%, RR 2.91, 95% CI 1.02 to 8.27; 1 study, 23 participants; very low-certainty evidence). It likely results in little to no difference in TTR (P = 0.19; 1 study, 23 participants; low-certainty evidence). The study did not measure QOL. OS was not reported for neoadjuvant immunotherapy (combined ipilimumab and nivolumab) when compared to neoadjuvant sequential immunotherapy (ipilimumab then nivolumab). Only Grade 3 to 4 immune-related AEs were reported; fewer were reported with combination treatment, and the sequential treatment arm closed early due to a high incidence of severe AEs. The neoadjuvant combination likely results in a higher ORR compared to sequential neoadjuvant treatment (60.1% versus 42.3%, RR 1.42, 95% CI 0.87 to 2.32; 1 study, 86 participants; low-certainty evidence). The study did not measure TTR and QOL. No data were reported on OS, AEs, TTR, or QOL for the comparison of neoadjuvant interferon (HDI) plus chemotherapy versus neoadjuvant chemotherapy. Neoadjuvant HDI plus chemotherapy may have little to no effect on ORR, but the evidence is very uncertain (33% versus 22%, RR 1.75, 95% CI 0.62 to 4.95; 1 study, 36 participants; very low-certainty evidence). Authors' conclusions: We are uncertain if neoadjuvant treatment increases OS or TTR compared with no neoadjuvant treatment, and it may be associated with a slightly higher rate of AEs. There is insufficient evidence to support the use of neoadjuvant treatment in clinical practice. Priorities for research include the development of a core outcome set for neoadjuvant trials that are adequately powered, with validation of pathological and radiological responses as intermediate endpoints, to investigate the relative benefits of neoadjuvant treatment compared with adjuvant treatment with immunotherapies or targeted therapies.
PUBLISHED
Keywords: Cancer; Immunology, Inflammation & Infection; Chronic Health Condition; Health